Synthesis and biological activity of ajoenes with increased aqueous solubility - Mabunda,Mandla (University of Cape Town, 2014)
The synthesis of four new ajoene analogues is presented in this thesis. The key to the synthesis was gaining access to a phenol derivative containing the ajoene core structure (sulfoxide / vinyl disulfide) that could be functionalised with various substituents. Evaluation of biological activity returned excellent in vitro activity against a WHCO1 oesophageal cell-line, in which a derivative with a methoxycarbonylmethylene substituent (PMB-ester) was shown to be the most active analogue that was fifteen times more active than Z-ajoene with an IC50 of 1.7 M. An aqueous solubility assay reveals that aqueous solubility increased with subsituition and the analogues with amido or acetate substituents were the most soluble ones. The analogues were also shown to enhance the apoptotic effects of two chemotherapeutic drugs Doxorubicin and Vincristine via chemosensitization. This effect was attributed to the presence of at least one p-methoxybenzyl substituent in the structure.